DIVERSIFIKASI PRODUK OLAHAN BERBASIS IKAN PATIN SEBAGAI POTENSI USAHA BAGI PANTI ASUHAN AL AMIN DAN SULTAN SURIANSYAH BANJARMASIN - Rizka Zulfikar; Prihatini Ade Mayvita (Universitas Islam kalimantan MAB, 2018)
The ideal condition of an orphanage is not always to rely on donations from year to year, but the orphanage itself is capable of generating additional funds independently, so that the orphanage is expected to be entrepreneurial whose outcome can help the operation of the orphanage. One potential and profitable business to be worked on by the orphanage is the business of diversification product from cat fish such as nugget and sausage considering catfish raw material is quite available and become one of the mainstay fishery products in Banjarmasin. The orphanage partners in this PKM programme are Al Amin Orphanage and Sultan Suriansyah Banjarmasin Orphanage and based on observation, several problems of partners that have been identified are as follows : (1) unmotivated santri to entrepreneurship so that santri have level very low self-sufficiency, (2) lack of knowledge of caregivers about entrepreneurship and information about business potentials that can be utilized to improve the welfare of the orphanage. In this programme, PKM activities are (1) to provide nugget and catfish sausage processing training (2) to provide assistance in the production, packaging and marketing process (3) to motivate to cultivate and entrepreneurial spirit with holding entrepreneurship motivation training, (4) conducting financial management training in the form of cost of goods production and production facilities, packaging and marketing for start up business.Keywords: Entrepreneurship, Cat Fish Products.